Meningkatkan Keaktifan dan Hasil Belajar Mata Pelajaran IPS dengan Menggunakan Metode Kooperatif Tipe Example Non Example Siswa Kelas VII-J SMP Negeri 1 Rancaekek Tahun Pelajaran 2018-2019 - Novianti, Yanti Riza (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this research is knowing how to succes the example non example method can improve students result ability in Learning IPS. Second purpose is to get the evidence the example non example method can improve students lerarning result and students learning activity. Based on the question of this study is how to improve students learning result and students learning activity using the example and non example leraning method. This study has four stage, there are planning, implementing, acting, observating and reflecting. There are two cycle in this study. Based on the result of this study from the cycle one and two using the test showed the cycle one is 17 students from 36 students who get more than 70 score, it showed the study success is (51,42%) while in cycle two the student who get more than 70 score is 30 students, it showed the study success is (80,22%)